Seasonal dynamics of the brown marmorated stink bug (Halyomorpha halys [Stål]) in an urban landscape - Tanja Bohinc; Luka Batistič; Stanislav Trdan (Acta Agriculturae Scandinavica. Section B, Soil and Plant Science)
During the 2021–2023 period, we investigated the seasonal dynamics of the brown marmorated stink bug (Halyomorpha halys) at two locations in an urban environment in central Slovenia. We have deployed three funnel traps, in combination with aggregation pheromone at each of the locations. We have recorded daily precipitation and average temperature. The pest was monitored at three different developmental stages, i.e. adults, young nymphs and old nymphs. Based on the average daily temperature, we have calculated degree day values (DD). We found that, accounting for the lower developmental threshold of 12.2°C, overwintered adults can appear in intervals, when DD reaches already 1°C till 11°C. Young nymphs appear when the DD value ranges from 290 to 516°C. Old larvae appear at DD values from 290 to 812°C, and adults of the first generation are observed when the DD value ranges from 809 to 1054°C. Our results revealed that brown marmorated stink bugs have one generation per year in Central Slovenia, and they are present in the landscape from April to the beginning of November. The results of our research are among the first in the field of seasonal dynamics of the brown marmorated stink bug in an urban environment.